Passive Fathometry in Shallow Waters of the Indian Continental Shelf. Issue 5 (2nd September 2016) - Najeem, S.; Latha, G.; Sanjana, M. C.; Kannan, R.
ABSTRACT: The present study demonstrates the use of ambient noise for estimating the ocean depth in shallow waters of the Indian continental shelf. Ocean depth is estimated using a technique known as passive fathometer processing, which involves the correlation of surface-generated ambient noise with its reflection from the seabed. Ambient noise data collected using a vertical array from four locations (off Cochin, off Cuddalore, off Kakinada, and off Goa) along the Indian continental shelf were used for the study. The noise data recorded during windy conditions within the frequency band of 200–5000 Hz were used for analysis. Both conventional and adaptive beamforming techniques were applied for the passive estimation of the ocean depth. The estimated water column depth using the ambient noise measurement shows good agreement with the known depth from all the four locations. The advantages and limitations of the adaptive processing technique have also been discussed. The study clearly demonstrates the application of the surface-generated ambient noise in seabed image processing.